Global Post-Authorization Safety Surveillance Study: real-world data on prophylaxis and on-demand treatment using FEIBA (an activated prothrombin complex concentrate). Issue 5 (July 2016) - Negrier, Claude; Voisin, Sophie; Baghaei, Fariba; Numerof, Robert; Novack, Aaron; Doralt, Jennifer E.; Romanov, Vadim; Gringeri, Alessandro
Abstract : This prospective, Post-Authorization Safety Surveillance (PASS) study was carried out in patients with hemophilia A or B and inhibitors treated with FEIBA for 1 year to collect real-world data on safety and effectiveness of FEIBA. The study followed a cohort design and did not make stipulations on treatment or observation schedule, as it was designed to observe routine medical practices based on physicians' treatment decisions, including whether patients received on-demand or prophylaxis with FEIBA. The attending physician maintained documentation, including medical records, laboratory reports, adverse event reports, and so on and a subject diary was used. Eighty-one patients were treated with FEIBA at 40 sites in 10 countries over a 4-year period. Sixty-nine patients (85.2%) had hemophilia A, two had (2.5%) hemophilia B, and ten (12.3%) had acquired hemophilia A. At baseline 45 patients (55.6%) were prescribed prophylaxis and 36 (44.6%) on-demand treatment. This study was novel in following safety and effectiveness in 'real world' on-demand and prophylactic use of FEIBA, and was able to collect data in these rare patients under routine clinical practice.